Exploring Reliability and Factorial Validity of Responsible Talk and its Impact on Cooperative Classrooms - Pons, Rosa M.; Reyes, Vicente (Frontiers in Education, 2021)
The aim of this study was to validate an instrument which enables the evaluation of talk which maximizes student performance during different segments of interaction-interactivity throughout a complete learning sequence. Based on works developed by the Learning and Research Development Center of the University of Pittsburgh, a scale was developed that gathered the most relevant behaviors of each proposed dimension by researchers from this university center. The scale was used to develop a core subject for a final year Bachelor of Arts degree in Primary Education at a university in Spain and was applied to the 65 students (M = 19, F = 46) taking the subject. The data analysis used an exploratory factor analysis (EFA) that yielded a reliability of α = 0.922. EFA revealed a final interpretable three-factor structure, and the factorial solution comprised 87.86% of total variance. Results show that the talk that students use has three purposes: to constitute an effective group for learning, to build knowledge and to verify its acquisition. The results are discussed in terms of input from the Center for Research in Education and Educational Technologies at the Open University and the Learning Research and Development Center of the University of Pittsburgh.